2011
DOI: 10.1111/j.1524-475x.2011.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid healing of chronic venous stasis leg ulcers treated by the application of a novel serum‐free cultured autologous epidermis

Abstract: The efficacy and durability of wound closure was examined in a prospective randomized unbalanced clinical trial using the application of a living serum-free cultured epidermal autograft in conjunction with wound-area debridement and a four-layer compression wrap (N=10) compared with wound-area debridement and a four-layer compression wrap in patients with hard-to-heal leg ulcers arising from confirmed venous stasis (N=5). All 15 patients who presented with full-thickness venous ulceration were treated weekly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In contrast, RepSox treatment did not enhance the growth of HEKs in a serum‐ and feeder‐free condition (Supporting Information Figure S2). Serum‐free monoculture can expand HEKs and has recently been implemented in therapies for small wounds . Co‐culture of HEKs on feeder cells, however, is still widely used for therapies involving major burn wounds that require much larger autografts .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, RepSox treatment did not enhance the growth of HEKs in a serum‐ and feeder‐free condition (Supporting Information Figure S2). Serum‐free monoculture can expand HEKs and has recently been implemented in therapies for small wounds . Co‐culture of HEKs on feeder cells, however, is still widely used for therapies involving major burn wounds that require much larger autografts .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a feeder‐free culture can reduce the time required for HEK expansion . However, although keratinocyte autografts prepared in a feeder‐free culture have been used in treating relatively small wounds, such as chronic venous leg ulcers, few burn units implement feeder‐free autografts for patients with severe burn wounds . An improved methodology to more rapidly expand keratinocytes with high proliferative potential in 3T3‐J2 co‐culture would reduce the number of surgical procedures and decrease hospitalization time for patients with massive burn injuries who undergo replacement by Green's method of skin covering nearly the entire body surface area.…”
mentioning
confidence: 99%
“…Differences in culture conditions and the use of various dermal components may account for differences in reported efficacy across the various single-cell and multi-cell autologous tissue constructs, but generally good results have been obtained using basic engineered tissue approaches [58][59][60][61] [60,62]. This product also showed good safety and efficacy, but the company filed for insolvency after failing to obtain necessary funding.…”
Section: Autologous Cell Approachesmentioning
confidence: 99%
“…It can be also used in combination with aesthetic procedures such as dermabrasion and laser resurfacing. Treatment of leg ulcers with cultured keratinocytes has been documented previously 7,8 and sprayed keratinocytes may provide a viable, cheaper alternative with fewer risks of morbidity.…”
Section: Sprayed Keratinocyte Suspension Therapymentioning
confidence: 99%